3D Printed Anatomical Nerve Regeneration Pathways. (18th September 2015) - Johnson, Blake N.; Lancaster, Karen Z.; Zhen, Gehua; He, Junyun; Gupta, Maneesh K.; Kong, Yong Lin; Engel, Esteban A.; Krick, Kellin D.; Ju, Alex; Meng, Fanben; Enquist, Lynn W.; Jia, Xiaofeng; et al.
Abstract : A 3D printing methodology for the design, optimization, and fabrication of a custom nerve repair technology for the regeneration of complex peripheral nerve injuries containing bifurcating sensory and motor nerve pathways is introduced. The custom scaffolds are deterministically fabricated via a microextrusion printing principle using 3D models, which are reverse engineered from patient anatomies by 3D scanning. The bifurcating pathways are augmented with 3D printed biomimetic physical cues (microgrooves) and path‐specific biochemical cues (spatially controlled multicomponent gradients). In vitro studies reveal that 3D printed physical and biochemical cues provide axonal guidance and chemotractant/chemokinetic functionality. In vivo studies examining the regeneration of bifurcated injuries across a 10 mm complex nerve gap in rats showed that the 3D printed scaffolds achieved successful regeneration of complex nerve injuries, resulting in enhanced functional return of the regenerated nerve. This approach suggests the potential of 3D printing toward advancing tissue regeneration in terms of: (1) the customization of scaffold geometries to match inherent tissue anatomies; (2) the integration of biomanufacturing approaches with computational modeling for design, analysis, and optimization; and (3) the enhancement of device properties with spatially controlled physical and biochemical functionalities, all enabled by the same 3D printing process. Abstract : An imaging‐coupled 3D printing methodology for the design, optimization, and fabrication of a customized nerve repair technology for complex injuries is presented. The custom scaffolds are deterministically fabricated via microextrusion printing, which enables the simultaneous incorporation of anatomical geometries, biomimetic physical cues, and spatially‐controlled biochemical gradients in a one‐pot 3D manufacturing approach.